Pengembangan Media Pembelajaran Infografis Berbasis Gambar Menggunakan Model Project Based Learning untuk Meningkatkan Kemampuan Menulis Puisi Kelas IV Sekolah Dasar pada Pelajaran Bahasa Indonesia - Yayanti; Abdul Muktadir; Agus Susanta (UNIB Press, 2024)
This research aims to create image-based infographic learning media using a project based learning model to improve the ability to write poetry in grade IV elementary school. The research was conducted at SDN 53 Bengkulu Tengah. This research is development research (Reseach and Development) with the ADDIE model. The research object is image-based infographic learning media in Indonesian language lessons on writing poetry. The instruments used were feasibility test questionnaires and teacher and student response test questionnaires. The feasibility test was carried out by 6 validators, namely 2 material experts, 2 language experts and 2 presentation experts. User response testing was carried out on 20 class IV students and 1 class teacher at SDN 53 Bengkulu Tengah. Data analysis is used to determine the validity of learning media using cross tabulation and questionnaire distribution. The results of the learning media feasibility test by the validator were reviewed from the material, language and presentation aspects, the material feasibility was 0.70 (feasible criteria), the language feasibility results were 0.90 (feasible criteria) and the display feasibility results were 0.80 (very feasible criteria). The results of the learning media field test by conducting posttests and pretests with the gain test results showing 20 students with a high gain criterion of 8 students with a percentage of 40%, then medium criteria of 11 students with a percentage of 55%, then low criteria of 1 student with a percentage of 5%. Apart from that, the results of interviews with class IV teachers showed a positive response. In other words, the learning media used can improve students' writing skills.